A Pilot Study Exploring the Relationship between Short-Term HRV and Self-Rated Health Status among Elderly People - Jia-Jen Chen; Li-Fan Liu; Jeen- Shin Wang; Ting-Ting Chang (Archives of Community Medicine and Public Health - Peertechz Publications, 2017)
Introduction: Establishing a personalized health care system can enable elderly people to access health care in their familiar community or home environments to achieve aging in place. The aims of this study are twofold:1) to explore the relationship between heart rate variability (HRV analysis) and subjective self-rated health status among elderly people, and 2) to examine whether HRV parameters serve as  lternative subjective-measure indices that can be used to detect and monitor the physical and mental health status of elderly people. Method: 101 adults aged 64-91 years old were included in the community. The 5-minute resting ECG was measured and participants were required to complete the Physical Activity for the Elderly (PASE), EuroQol-5D ( EQ-5D) and Chinese Health Questionnaire-12 (CHQ). Results: The correlation analysis showed HRV index (LF/HF ratio) had a positive relationship with age and CHQ, but negatively correlated with BMI. The clustering analysis also showed subgroup III (frail roup) had the characteristics of being older and having lower BMI, lower physical levels, poor quality of life and self-rated health compared with subgroups I and II (relatively young and normal groups, respectively). Also, we found that the LF/HF ratio might be negatively correlated with EQ utility in subgroups II. Positive relationships were observed between HRV indices such as RMSSD, LF, HF and CHQ in subgroup III. Discussion: HRV represents not only an objective biomarker but also a potential candidate for evaluating self-rated health. Development and utilization of HRV devices to establish a personalized health care monitoring system can achieve successful aging in the community among elderly people.